2003
DOI: 10.1111/1468-5965.00414
|View full text |Cite
|
Sign up to set email alerts
|

Why European Commissioners Matter*

Abstract: Discussions of the role European Commissioners play in European Union politics are shaped by three powerful implicit assumptions. These posit a causal relationship between a Commissioner's behaviour and previous career, portfolio and national origin. In addition, Commissioners are seen as exacerbating the fragmentation of the European Commission as a whole. Based on an empirical study of eight Commissioners from the Delors II and the Santer colleges, this article challenges or reformulates these assumptions. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…While there exist many papers detecting such relations for legislative bodies, barely any work has been done to investigate the role of an executive institution in an international organization. We also build on recent, mostly qualitative work, which started to examine the behavior of the individual actors who form the EC (see for instance Smith 2003;Wonka 2007), by assessing the influence of the EU Commissioners for Agriculture on the share of EU spending received by their home countries quantitatively.…”
Section: A Leader Origin and Distributive Financial Decision Makingmentioning
confidence: 99%
“…While there exist many papers detecting such relations for legislative bodies, barely any work has been done to investigate the role of an executive institution in an international organization. We also build on recent, mostly qualitative work, which started to examine the behavior of the individual actors who form the EC (see for instance Smith 2003;Wonka 2007), by assessing the influence of the EU Commissioners for Agriculture on the share of EU spending received by their home countries quantitatively.…”
Section: A Leader Origin and Distributive Financial Decision Makingmentioning
confidence: 99%
“…While Andy Smith (2003) relies on interviews (conducted in two waves with a sample of commissioners), the larger body of research concentrates on shifting loyalties and allegiances at the bureaucrat level. These bureaucratfocused research projects concentrate on two types of expert: (i) national-level experts that are members of Commission and Council committees, and (ii) permanent officials in the Commission.…”
Section: Existing Research Designs and Qmentioning
confidence: 99%
“…We are more concerned with who the interviewees (P-set) are, than the quantity of interviewees. In the case of our study, the P-set could be identified as members of a particular committee or DG or indeed commissioners themselves (as Smith 2003). The next step is to define the distribution (see Figure 2).…”
Section: The Q Processmentioning
confidence: 99%
“…Cini 1996;Page 1997;Hooghe 2001;Smith 2003). The Commission's role as a 'policy entrepreneur' and its formal and informal agenda setting powers (Pollack 1998), as well as its pivotal position as central administrative body of the European Union, constitute important areas of study for understanding the European integration process.…”
Section: Agency Within the European State Formationmentioning
confidence: 99%